Features of use of combinational circuits play in attack during volleyball matches - Artemenko, B. O. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
Purpose : To characterize tactical formation game action in the attack and the frequency of execution of power and tactical (planning) innings volleyball players of different skill levels. Material and methods: The analyzed video recordings of volleyball matches with the strongest teams of the world: Brazil, Russia, USA, Cuba, Italy, the leading volleyball championship teams of Russia and Ukraine. The features of tactical formation game. Results: It was established that the binders players strongest teams and club teams in the world is used in the organization of attack more variety of tactical combinations. So almost equally, the following combinations: Rise, Pipe and Zone (13.4 % 12.6 % 11.5%). Ukrainian binders players prefer only combinations Rise - 23%; Pipe - 2%; Zone - 2.5%, respectively. Distribution innings for planning and power for Ukrainian teams: 59.7 % versus 40.3% and 27.5 % versus 72.5 %, respectively, the strongest national teams in the world. Conclusions: The features of tactical formation attack suggest the best technical - tactical training players tie the strongest teams in the world and the whole team. Also leading the team to the world is much more likely to use the power supply, which indicates the nature of the power of world volleyball.